Beyond the forest plot: The drapery plot. (30th April 2020) - Rücker, Gerta; Schwarzer, Guido
Abstract : In the era of the "reproducibility crisis" and the " P ‐value controversy" new ways of presentation and interpretation of the results of a meta‐analysis are desirable. One suggestion that has been made for single studies almost six decades ago and taken up now and then is the P ‐value function. For a given outcome, this function assigns a P ‐value to each possible hypothetical value, given the data. Moreover, the P ‐value function simultaneously provides two‐sided confidence intervals for all possible alpha levels. An application to meta‐analysis, while suggested early, has not been widely established. We introduce the drapery plot that presents the P ‐value function for all individual studies and pooled estimates in a meta‐analysis as curves and the prediction range for a single future study. We also present a scaled variant with the test statistic on the y‐axis. Both plots visualize the full information of a pairwise meta‐analysis. We see a drapery plot as a complementary figure to a forest plot. It may be even an alternative in meta‐analyses with many studies where forest plots tend to become very large and complex.